Upaya Perancangan Peningkatan Availability Mesin Lem dengan Single Minute Exchange of Die (SMED) di Line 1 CV. Sinar Baja Electric: Sebuah Studi Kasus - Justyn Riccardo Lie; Nova Sepadyati (Jurnal Titra, 2022)
Changeover is the time needed to prepare for the next product production. CV. Sinar Baja Electric has a high changeover time due to the many product variants. A high changeover indicates a low level of machine availability. This study aims to increase the availability value of the company. This research will use OEE and SMED methods. Overall equipment effectiveness is a way to monitor and improve the efficiency of the manufacturing process. There are 3 factors that influence the calculation of OEE, namely availability, performance, and quality. Single Minute Exchange of Die (SMED) is a method used to reduce changeover time when a machine or equipment is undergoing a product type change. The purpose of using this method is to reduce changeover time. Based on the results of data processing, it was found that the proposed improvements for reducing the standard range from setting the glue timer and air pressure, improving the time sequence of production scheduling based on the size and type of glue, reducing the variant of glue used, setting the location and increasing the number of scales, making a structured work instruction setup machine. Estimated proposal to get a changeover time reduction of 55.2%